Personality and Serum Lipids: Does Lifestyle Account for Their Concurrent and Long‐term Relationships. Issue 6 (11th October 2013) - Armon, Galit
Abstract This study evaluates concurrent and over time associations of personality with measures of three serum lipids associated coronary heart disease morbidity, namely, high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein cholesterol and triglyceride (TRI). Participants were individuals who underwent a health examination at two points of time, T1 (N = 3835) and T2 (N = 2283), about 2.5 years apart. Personality was assessed by the Five‐Factor Model. Health, socioeconomic status and healthy lifestyle behaviours (smoking intensity, physical activity and body weight) were controlled. Regression analyses indicate that the personality factors of neuroticism, extraversion and conscientiousness are each significantly associated with HDL‐C and TRI, both concurrently and over time. However, most of these associations decreased to marginal significance when adjusted for body weight or physical activity as possible mediators. Both concurrent and over time associations of the openness personality trait with HDL‐C and TRI were significant and persisted after adjustment for measures of a healthy lifestyle. This study emphasizes the importance of collecting measures of a healthy lifestyle to better understand how personality might influence serum lipids. Copyright © 2013 European Association of Personality Psychology